Neoconservadorismo, política e armas : a literatura e as organizações pró-armas dos Estados Unidos e a sua influência nos discursos da bancada da bala no Congresso Nacional - Vechi, Fernando (2023)
The purpose of this work was to analyze the formation of the discourse in favor of guns in Brazil, observing how the discussions and developments of the American neoconservative movement and its armaments ideology impact the debates of the Chamber of Deputies in Brazil, precisely influencing the federal deputies of the so-called Bancada da Bala, not only in his performance in parliament, but on social networks, especially on Twitter. Starting from the concepts of punitive populism and moral panic, we sought to understand the scenario of public security and criminal policy carried out in the Brazilian legislature. In this context, a bibliographical research was carried out, bringing together the most representative discourses of the literature and organizations of the United States pro-guns and, subsequently, of the Brazilian arms literature. Then, we analyzed the speeches favorable to the armament present in the sessions and meetings of the Chamber of Deputies about the Projects of Law n. 1,555/2003 and n. 3,722/2012, relating them to the arguments found in foreign and national literature and the debates carried out by international and national organizations interested in facilitating the use of weapons. In this line, analyzing a later moment, the research sought to identify who are the deputies of the 56th legislature who belong to the group called Bancada da Bala and sought to present the main bills defended by these parliamentarians, especially with regard to the flexibility of the Law n. 10.826/2003, the Disarmament Statute. Finally, through a critique of the concepts of etiological criminology and the ideology of social defense, as well as the neoconservative theory, the objective was to observe the manifestations of the said caucus on social networks, with a focus on Twitter. For this undertaking, the method of Dialogical Discourse Analysis was used to interpret the tweets of pro-gun Brazilian deputies in the years 2019 and 2020. The results obtained demonstrate the ideological alignment of the Balcada da Bala of the Federal Chamber with the American neoconservative movement, with manifestations that have specific characteristics, in a movement called Bolsonarism.